PENGARUH MEDIA INTERAKTIF BERBASIS WORDWALL TERHADAP MOTIVASI BELAJAR SISWA KELAS IV DI SD NEGERI NEGLA PADA MATA PELAJARAN IPAS - Rahma Nur Ngaini (STKIP Subang, 2025)
This study aims to examine the effect of Wordwall-based interactive media on students’ learning motivation in IPAS learning aligned with the Merdeka Curriculum. This research employed a quantitative approach using a quasi-experimental one group pretest–posttest design. The participants consisted of 25 fourth-grade students at SD Negeri Negla. Data were collected using a learning motivation questionnaire and analyzed using paired sample t-test and N-Gain analysis. The results showed a significant increase in students’ learning motivation (t = 6.21; p < 0.05) with a moderate N-Gain score (0.46). These findings indicate that Wordwall is effective in enhancing students’ learning motivation in elementary IPAS learning.